The impossible lives of Greta Wells - Greer, Andrew Sean (Ecco, 2013)
"After the death of her beloved twin brother, Felix, and the breakup with her longtime lover, Nathan, Greta Wells embarks on a radical psychiatric treatment to alleviate her suffocating depression. But the treatment has unexpected effects, and Greta finds herself transported to the lives she might have had if she'd been born in different eras."--from publisher's description.